ANALISIS KEPATUHAN PENGUSAHA KENA PAJAK (PKP) DALAM MELAKSANAKAN KEWAJIBAN PERPAJAKANNYA BERDASARKAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN PADA SEKTOR PAJAK PERTAMBAHAN NILAI (PPN) DI MANADO - Mokoagow, Selviani; Nangoy, Grace; Warongan, Jessy D. L. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to analyze Taxable Entrepreneurs (PKP) compliance in carrying out its tax obligations based on the implementation of modernization of the tax administration system, the obstacles are hindering it and the efforts made to overcome the obstacles faced by Taxable Entrepreneurs (PKP) in carrying out tax obligations based on the modernization of the tax administration system. The research method used is a qualitative research method with a case study approach. This study uses the Miles and Huberman Model data analysis technique which consists of data reduction, data presentation and conclusion drawing and verification. The results showed that in fulfilling their tax obligations, Taxable Entrepreneurs (PKP) implements them based on applicable regulations, complies with the specified conditions, that is the timeliness of taxpayers carrying out tax obligations, not having tax arrears, not committing tax crimes, and doing bookkeeping. However, there are still obstacles that hinder, such as, the network of the Directorate General of Taxes (DGT) which is busy making it difficult to access. This also causes delays in reporting VAT Returns (SPT). This also causes the system at the bank and post office to be unavailable or disconnected when payment is to be made. To overcome these obstacles, taxpayers try to fulfill their tax obligations before the specified time limit in order to avoid the busy DGT network. In addition, using the services of a tax consultant whose job is to assist and guide taxpayers is a Taxable Entrepreneurs (PKP) effort in fulfilling VAT obligations.